The disabled tyrant's beloved pet fish. 3 - Xue Shan Fei Hu (Canji Baojun De Zhangxin Yu Chong, 2024)
When Prince Jing is sent to quell the disturbance at the western border, there’s no question that Li Yu will accompany him—as his boyfriend and as his pet fish! Li Yu’s mission is to help Prince Jing secure his position as heir to the throne. However, the new couple is in for a surprise when Li Yu makes a much bigger splash in the imperial line of succession: even male fish can lay eggs now!